2013
DOI: 10.1007/jhep10(2013)100
|View full text |Cite
|
Sign up to set email alerts
|

Euclidian 4d quantum gravity with a non-trivial measure term

Abstract: Abstract:We explore an extended coupling constant space of 4d regularized Euclidean quantum gravity, defined via the formalism of dynamical triangulations. We add a measure term which can also serve as a generalized higher curvature term and determine the phase diagram and the geometries dominating in the various regions. A first order phase transition line is observed, but no second order transition point is located. As a consequence we cannot attribute any continuum physics interpretation to the so-called cr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 55 publications
8
57
0
Order By: Relevance
“…The Hausdorff dimension of a branched polymer is expected to be 2, a result that is confirmed by our previous calculations [18]. The spectral dimension of the branched polymer phase is expected to be D S = 4/3, a result that has also been numerically confirmed [17,18]. Once again, the properties of this phase make it a poor candidate for recovering four-dimensional space-time.…”
Section: Phase Diagramsupporting
confidence: 56%
See 2 more Smart Citations
“…The Hausdorff dimension of a branched polymer is expected to be 2, a result that is confirmed by our previous calculations [18]. The spectral dimension of the branched polymer phase is expected to be D S = 4/3, a result that has also been numerically confirmed [17,18]. Once again, the properties of this phase make it a poor candidate for recovering four-dimensional space-time.…”
Section: Phase Diagramsupporting
confidence: 56%
“…Early work that included a nontrivial local measure term with a new arbitrary coupling identified a region of the extended phase diagram with properties that appeared to be different from the previously identified phases [20,21]; this was dubbed the crinkled region. However, follow-up studies showed that the crinkled region did not have desirable features, like a dimension close to four, suggesting that the crinkled region was most likely a part of the collapsed phase with particularly large finite-size effects [17,18]. The presence of a cross-over rather than a genuine phase transition between the collapsed phase and the crinkled region further supported this conclusion.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…The DT formalism was extended to higher dimensional gravity [20][21][22][23][24][25][26][27], but there it was less successful [28,29]. It is not ruled out that the theory can provide us with a successful version of quantum gravity, but if so the formulation has to be more elaborate than the first models (see [30][31][32][33] for recent attempts). However, there is one modification of DT which seems to work in the sense that lattice theory might have a non-trivial continuum limit, the so-called Causal Dynamical Triangulations model (CDT).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a first step connecting the NGFP to the underlying conformal field theory appeared in [64], possible completions of the flow at low energy have been discussed in [17,24,38,40,41] and geometric arguments determining the scaling of Newton's constant at the NGFP have been forwarded in [65,66]. In parallel Monte Carlo approaches to quantum gravity including Causal Dynamical Triangulations [67][68][69][70][71][72][73][74][75], Euclidean Dynamical Triangulations [76][77][78][79][80] and Lattice Quantum Gravity [81,82] made vast progress towards constructing phase diagrams at the non-perturbative level. While it is conceivable that all of these approaches probe the same universal short distance physics, a unified picture has yet to emerge.…”
Section: Introductionmentioning
confidence: 99%